A novel multimodal nanoplatform for targeting tumor necrosis. Issue 47 (15th September 2021) - Han, Xiangjun; Taratula, Oleh; St Lorenz, Anna; Moses, Abraham S.; Albarqi, Hassan A.; Jahangiri, Younes; Wu, Qirun; Xu, Ke; Taratula, Olena; Farsad, Khashayar
Abstract : Au-Hyp-NP developed by encapsulation of gold and hypericin into PEG-PCL nanoplatform for fluorescence and X-ray tracking with tumor necrosis targeting. Abstract : Peri-necrotic tumor regions have been found to be a source of cancer stem cells (CSC), important in tumor recurrence. Necrotic and peri-necrotic tumor zones have poor vascular supply, limiting effective exposure to systemically administered therapeutics. Therefore, there is a critical need to develop agents that can effectively target these relatively protected tumor areas. We have developed a multi-property nanoplatform with necrosis avidity, fluorescence imaging and X-ray tracking capabilities to evaluate its feasibility for therapeutic drug delivery. The developed nanoparticle consists of three elements: poly(ethylene glycol)- block -poly(ε-caprolactone) as the biodegradable carrier; hypericin as a natural compound with fluorescence and necrosis avidity; and gold nanoparticles for X-ray tracking. This reproducible nanoparticle has a hydrodynamic size of 103.9 ± 1.7 nm with a uniform spherical morphology (polydispersity index = 0.12). The nanoparticle shows safety with systemic administration and a stable 30 day profile. Intravenous nanoparticle injection into a subcutaneous tumor-bearing mouse and intra-arterial nanoparticle injection into rabbits bearing VX2 orthotopic liver tumors resulted in fluorescence and X-ray attenuation within the tumors. In addition, ex vivo and histological analysis confirmed the accumulation of hypericin and gold in areas of necrosis and peri-necrosis. This nanoplatform, therefore, has the potential to enhance putative therapeutic drug delivery to necrotic and peri-necrotic areas, and may also have an application for monitoring early response to anti-tumor therapies.